Clinical trials and evaluation of Cardiac Ultrasonography over 4G Wireless Network using a Tele-operated Robot - Avgousti, Sotiris; Masouras, Panicos; Panayides, Andreas S.; Pattichis, Constantinos S.; Christoforou, Eftychios G.; Vieyres, Pierre; Novales, Cyril (My University, 2017)
The experimental setup of a wearable tele-echography robot the MELODY system over a 4G connectivity link used to measure the system performance is presented. The evaluation and investigation of the relevant medical ultrasound video and the relevant issues defined in terms of the average throughput, and jitter delay are investigated. A comprehensive video coding standards comparison for cardiac ultrasound applications is performed, including H.264/AVC and HEVC using a data set of nine cardiac ultrasound videos. Both objective and subjective (clinical) video quality assessment were performed
Keywords: 4G; Mobile Communication; HEVC; H.264; MPEG4; MPEG2; VIDEO CODING